Pharmacists' involvement in COVID-19 vaccination across Europe: a situational analysis of current practice and policy - OKUYAN, BETÜL (SPRINGER, 2022)
One year since the emergence of the COVID-19 pandemic, rapid response measures have been implemented internationally to mitigate the spread of the virus. Following rapid and successful pre-clinical and human trials, several vaccines have been authorised for use across Europe through the European Medicines Agency and national regulatory authorities. Clinical trials have shown promising results including important reductions in disease severity, hospitalisation and mortality. In order to maximise the public health benefit of available vaccines, there is a pressing need to vaccinate a large proportion of the population. Internationally, this has prompted coordination of existing services at enormous scale, and development and implementation of novel vaccination strategies to ensure maximum inoculation over the shortest possible timeframe. Pharmacists are being promoted as healthcare professionals that enhance roll-out of COVID-19 vaccination programmes. This paper aims to summarise current policy and practice in relation to pharmacists' involvement in COVID-19 vaccination in 13 countries across Europe.
Keywords: Coronavirus; COVID-19; Pharmacist; Pharmacy; Public health; Vaccine